Principal Leadership and School Culture in Enhancing Teacher Productivity: Integrating Islamic Values and Local Culture at SMA Negeri 2 And SMA Negeri 3 Yogyakarta - Muh. Ainul Basyirah; Lia Yuliana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Education plays a strategic role in improving the quality of human resources, particularly through effective school leadership and organizational culture. However, previous studies tend to examine principal leadership and teacher performance separately, without integrating Islamic values and local cultural contexts. Therefore, this study focuses on analyzing principal leadership strategies and school culture in improving teacher performance within the context of Indonesian education. This study aims to examine how leadership strategies and school culture interact in enhancing teacher performance at SMA Negeri 2 Yogyakarta and SMA Negeri 3 Yogyakarta. The scope of this study includes leadership practices, school culture, and the integration of Islamic and local cultural values. This research employed a qualitative approach with a descriptive design. Data were collected through observations, in-depth interviews, and documentation involving principals, teachers, and educational staff. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, supported by triangulation techniques to ensure validity. The findings indicate that democratic and transformational leadership strategies improve teacher discipline, motivation, and innovation as key dimensions of teacher performance. Islamic values such as amanah, discipline, and shura, along with local cultural values like gotong royong and unggah-ungguh, contribute to a positive and productive school environment.